Revealing ideal number of children by households: A socioeconomic analysis using Pakistan demographic and health survey - Rana Ejaz Ali Khan; Khadija Malik Bari (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
Most of the developing economies including Pakistan are facing the problem of rapid population growth. All the efforts to control higher population growth become useless when the household desire larger number of children. In the study the determinants of ideal number of children revealed by the woman are probed. So along with sociocultural, economic, demographic and attitudinal characteristics of the household, a range of woman characteristics like her education, working status, BMI, exposure to media, ownership of assets, household decision-making, justification of violence and spousal age difference are included in the model. The results have shown that woman's education, woman's empowerment through household decision-making and resistance to violence against woman and inter-spousal age difference reduce the number of desired children. Exposure to media regarding the family planning programs has also shown negative impact on the ideal number of children. Wealth index has also been emerged as the strong predictor for keeping the ideal number of children low. On the other hand, son-daughter ratio and good health of the woman proxied by BMI positively impact the ideal number of children. From the policy perspective woman's education, exposure to media and woman autonomy needs specific attention at the end of family planning programs and women development in Pakistan.
Keywords: 330; Fertility; Woman empowerment; Household wealth; Female education; Media exposure; Family planning